Disentangling the Crime-arrest Relationship: The Influence of Social Context - Chamlin, Mitchell B. (Journal of quantitative criminology, 2009)
Drawing on the economic and conflict perspectives of crime control, as well as insights from the tipping effect literature, the present investigation examines the extent to which the social context within which potential offenders operate tempers the macro-level, reciprocal relationship between crime and arrests. We use autoregressive integrated moving average techniques to assess the extent to which the April 2001 race-related riot in Cincinnati, Ohio conditions the reciprocal relationship between property crime and arrests for the entire city and disaggregated by police district. Consistent with a majority of prior longitudinal studies, our analyses for the entire length of the times series reveal no evidence of an association between our measures of crime and arrest, regardless of the level of spatial aggregation. In contrast to the results from our baseline models, the post-riot transfer function models indicate that there is a reciprocal association between crime and arrests that is contingent upon the social context. The implications of our findings for the further study of the reciprocal relationship between crime and arrests are discussed.